Macular thickness assessment of healthy eye based on ethinicity among school children using optical coherence tomography (OCT) / Siti Nor Hajar Mohd Zulkifli - Mohd Zulkifli, Siti Nor Hajar (2015)
This study examined the normal range of macular thickness in Malay, Chinese and Indian children using Spectral-Domain Optical Coherence Tomography (SO-OCT). This study comprised of sixty children recruited from several primary schools situated within 14 kilometers from UiTM Puncak Alam as the representative population of the residential area. Subjects aged between 10 and 11 were ensured to have best corrected visual acuity of 6/9 or better in either eye, have range of refractive error between +3.00 DS to -3.00DS with astigmatism ± 3.00 DC and both parents are of same races. Macular thickness among the subjects were examined according to their race. The total macular thickness for all children is recorded at 7.449J..lrn ± 0.363 and the foveal thickness was 247.05J..lm ± 33.26. The foveal thickness stratified by race has shown that the Malay (250.79J..lm ± 38.56) and Chinese children (253.77J..lrn ± 28.43) have almost similar thickness while Indian children have the thinnest with mean of 238.08J..lm ± 25.54. Though the differences of overall total macular volume between races is not significant, it was found out that there are dissimilarities in macular thickness structurally, thus suggests that race (Malay, Chinese and Indian) and macular thickness is interrelated. It is strongly recommended that further research can be carried out on larger samples to get more accurate results.